Evaluation of Women’s Perceptions toward Wellness - Abdulwahid, hala (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): To evaluate women’s perceptions toward wellness. Methodology: A descriptive-evaluation design is employed through the present study to evaluate women’s perceptions toward wellness in Baghdad City. A non-probability (purposive) sample of (140) woman is selected from three primary health centers in Baghdad City. A questionnaire, of (57) items, is designed and constructed for the purpose of the study. Split-half internal consistency reliability of the study instrument is determined through computation of Cronbach alpha correlation coefficient and the content validity of the instrument determined through a panel of (8) experts. Data are collected with the study instrument and the interview technique as means of data collection. Data are analyzed by using the descriptive statistical data analysis approach of frequency (F), percentage (%), total score and mean of scores (MS). Results: The findings of the study reveal that the majority of women have good level of perceptions toward the five dimensions of wellness. Such perception can affect positively and definitely on their overall health. Recommendations: The study recommends further researches regarding evaluating women’s lifestyle toward wellness.